Quality Control system for a hot-rolled metal surface - I. Mazur; T. Koinov (Fracture and Structural Integrity)
The modern ideas about of quality of products are based on the principle of the absolute satisfaction of requirements of recommendations of the buyer. A presence of surface defects of steel-smelting and rolling origin is peculiar to the production of hot-rolling mill. The automatic surface inspection system (ASIS) includes two digital line video cameras for the filming of the upper and lower surfaces of the flat bar, block of illumination of the upper and lower surfaces of the flat bar, computer equipment. A system that secures 100 % control of the surface of rolled metal (of the upper and lower side) detects automatically and classifies the sheet defects in the real time mode was mounted in the domestic practice in the first time in 2003 on hot rolling mill 2000 JSC «Novolipetsk Iron & Steel Corporation» (NISC). The whole assortment of the mill 2000 was divided for the five groups by the outward appearance of the surface. The works on the identification of defects of hot-rolled metal and widening of data base of knowledge of ASIS were continued after the carrying out of guarantee tests. More than 10 thousand images of defects were added to the data base during the year.